2017
DOI: 10.1186/s12957-017-1230-4
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib-loaded DSPE-PEG2000 nanomicelles with CD133 aptamers target lung cancer stem cells

Abstract: BackgroundLung cancer stem cells (CSCs) are considered to be the seed of lung cancer, and CD133 is a marker of lung CSCs. Here, we developed gefitinib-loaded poly(ethylene glycol) 2000-distearoylphosphatidylethanolamine nanomicelles with CD133 aptamers (M-Gef-CD133) to eliminate CD133+ lung CSCs.MethodsM-Gef-CD133 was prepared using a lipid-film-based approach. The targeting and activity of M-Gef-CD133 towards lung CSCs were evaluated.ResultsM-Gef-CD133 were small (25 nm) and showed enhanced cytotoxic effect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 42 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…In addition, CD133 + lung cancer cells have been indicated to highly express a variety of stemness genes (5,6). A previous study by our group also confirmed that CD133 + lung cancer cells expressed high levels of stemness genes and had increased tumorigenicity in mice compared with CD133-lung cancer cells, suggesting that CD133 + lung cancer cells exhibited lung cancer-initiating cell properties (7). However, tumors may consist of multiple genetically or phenotypically distinct types of cancer-initiating cells.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, CD133 + lung cancer cells have been indicated to highly express a variety of stemness genes (5,6). A previous study by our group also confirmed that CD133 + lung cancer cells expressed high levels of stemness genes and had increased tumorigenicity in mice compared with CD133-lung cancer cells, suggesting that CD133 + lung cancer cells exhibited lung cancer-initiating cell properties (7). However, tumors may consist of multiple genetically or phenotypically distinct types of cancer-initiating cells.…”
Section: Introductionsupporting
confidence: 62%
“…Polyethylene glycol 2000-distearoyl phosphatidylethanolamine (DSPE-PEG2000) nanomicelles are promising due to their particularly small size (~20 nm), good biocompatibility and superior penetration into solid tumors (1416). In a previous study by our group, CD133 aptamer-conjugated gefitinib DSPE-PEG2000 nanomicelles (CD133-NM-Gef) were constructed to enhance the delivery of gefitinib into lung tumors (7). In the present study, to achieve simultaneous targeting of nanomicelles to CD44 + and CD133 + cancer cells, CD44 aptamers were further conjugated to CD133-NM-Gef to develop CD133 and CD44 aptamer-conjugated nanomicelles loaded with gefitinib (CD133/CD44-NM-Gef).…”
Section: Introductionmentioning
confidence: 99%
“…To determine the self-renewal ability of A549/PTX CD133 + cells and CD133 - cells, we performed sphere formation assays, which are performed to identify stem cells via their capacity of self-renewal and differentiation at the levels of single cells [ 28 ]. As shown in Figure 2A and 2B , the number and size of the spheres formed by CD133 + cells were significantly larger compared with those formed by CD133 - cells, indicating that A549/PTX CD133 + cells have a higher self-renewal capacity than CD133 - cells.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, targeting CSCs based on their specific biomarkers is unquestionably a rational choice, and correspondingly, a great amount of biomarkers-mediated delivery carriers and systems have been developed and explored. Table 2 24 , 25 , 26 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 presents an overview of recent representative drug delivery carriers and systems. CD44 is one of the most famous surface markers related to CSCs, and HA is the main component of the extracellular matrix, especially as it is abundantly expressed in a wide variety of CSCs and has a high affinity for CD44 receptors and better biocompatibility than anti-CD44 antibody 91 .…”
Section: Ddss For Direct Targeting Of Cscs At the Cellular Levelmentioning
confidence: 99%